Development and Validation of a Screening Protocol to Identify Elder Abuse in United States Emergency Departments, Chapel Hill, North Carolina, Camden, New Jersey, and Jacksonville, Florida, 2018-2019 - Platts-Mills, Timothy ([Verlag nicht ermittelbar], 2021)
This study was conducted to address elder abuse within emergency departments in the United States. The aim of this study was to develop a screening protocol or more specifically, an emergency department based tool to discover this specific abuse and try to eliminate it. This emergency department senior aid tool was created in two phases: the development phase and the validation phase. The purpose of the development phase was to test the reliability of this tool in detecting elder abuse in ages 65 and older individuals. On the other hand, the validation phase was to test the tool at three different locations: UNC Medical Center in Chapel Hill, North Carolina, Cooper Hospital in Camden, New Jersey, and University of Florida Health in Jacksonville, Florida.